No association between incidence of type 1 diabetes and rotavirus vaccination in Swedish children - Rangert, Amanda; Oldin, Carin; Golsäter, Marie; Ludvigsson, Johnny; Åkesson, Karin (Frontiers in Immunology, 2023)
Background Rotavirus infection is a potential trigger of type 1 diabetes (T1D) and rotavirus vaccination is hypothesized to decrease the incidence of T1D. In Sweden, rotavirus vaccination was introduced in 2014 in two regions and from 2019, nationwide. This study aims to investigate the association between rotavirus vaccination and incidence of T1D in Swedish children and whether rotavirus vaccination is associated with a change in clinical manifestation at diabetes onset. Methods A nationwide register-based study with all Swedish children <15 years of age, diagnosed with T1D 2009-2019 was conducted. 7893 children were retrieved. Nationwide vaccine coverage was collected from Child Health Services. Three vaccine groups were created: I: Vaccination start 2014; II: Gradual vaccination start 2016-2018; III: No vaccination. Incidence rates of T1D before (2009-2014) and after (2014-2019) introduction of rotavirus vaccine were compared. Findings The mean incidence of T1D in children <15 years was 42·61 per 100 000 during the observed period. When comparing the years before and after 2014 the incidence rate ratio (IRR) for children <5 years was 0·86 in group I (p=0·10), 0·85 (p=0·05) in group II and 0·87 (p=0·06) in group III. A similar IRR reduction was also seen among older children who received no vaccine. Children developing or not developing T1D were vaccinated to the same extent. No differences regarding clinical manifestation at onset associated with rotavirus vaccination were seen. Interpretation There is no association between rotavirus vaccination in children and incidence or clinical manifestation of T1D.